Impact of online lottery sales prohibition on the structure of lottery consumers: A time cost perspective in China - Zeyu Feng (PLoS ONE, 2025)
Lottery public welfare funds constitute a significant source of government fiscal revenue. Consequently, it is of crucial importance to objectively analyze the impact of purchasing convenience on the lottery industry. This study employs the discrete-time dynamic optimization Bellman equation to examine the influence of time costs associated with purchasing lottery tickets on consumer demand across different income groups, considering various types of lottery tickets. Utilizing panel data spanning from 2007 to 2021 from 30 provinces in China, the Difference-in-Differences (DID) method is employed to assess the effects of the ban on online lottery sales, implemented in 2015, on the sales of welfare and sports lottery tickets in distinct income regions. The findings indicate that the prohibition of online lottery sales leads to a more rapid decline in the demand for betting-lottery tickets in high-income areas compared to low-income areas, while no significant variation in the rate of decline in demand for lotto-lottery tickets is observed. This trend hampers the improvement of the lottery consumer structure and overall sales. The research outcomes furnish valuable references for enhancing the structure of lottery consumers and augmenting sales within the lottery industry.